A full-textile triboelectric nanogenerator with multisource energy harvesting capability. (1st September 2022) - Cao, Yuying; Shao, Hao; Wang, Hongxia; Li, Xiang; Zhu, Mingkang; Fang, Jian; Cheng, Tinghai; Lin, Tong
Graphical abstract: Highlights: A full-textile TENG with high air-permeability and good softness is developed. The TENG can convert sound, wind, and human motion into electrical energy. The device under mechanical impact can generate 897.60 V open-circuit voltage. The acoustoelectric conversion modeling agrees with the experimental results. Abstract: This study develops a full-textile triboelectric nanogenerator to harvest energy from multiple sources, such as sound, human motion, and wind, individually. The textile device consists of three layers, an elastic electrically conductive fabric knitted by silicone-coated yarn as the negative component and electrode, a commercial silk fabric as the positive component, and a conductive fabric as the second electrode. Under the mechanical impact (force ∼50 N, frequency 3 Hz), the device can generate 888.08 ± 4.75 V peak-to-valley voltage, 2.01 ± 0.50 μA short-circuit current, and 138.55 mW/m 2 maximum instantaneous power density. It can also convert low-frequency sound (e.g., 75 Hz) into 174.66 ± 2.59 V peak-to-valley voltage (short-circuit current 6.62 ± 0.13 μA, maximum instantaneous power density 19.4 mW/m 2 ). We also used the forced vibration analysis and the intrinsic output characteristics to model the acoustoelectric conversion. The modeling showed good agreement with the experiment results. We further demonstrated the ability to harvest energy from multisource individually, such as airborne noise generated by a working machine, human motion, and wind. The electrical power generated can run commercial electronic devices (e.g., 37 LEDs) or accumulate in a capacitor. In addition, the device has high air permeability and good softness. It may be useful for developing wearable energy generators for various high-tech applications.